Nursing Students’ Perceptions of Smartphone Use in the Clinical Care and Safety of Hospitalised Patients - Gutiérrez-Puertas, Vanesa (Int J Environ Res Public Health, 2021)
Smartphones have become an indispensable item for nursing students. The use of these devices in the clinical setting could have various effects on the clinical work of nursing students. This study was to explore nursing students’ perceptions of their lived experiences of smartphone use in the clinical setting, in regard to patient safety. A descriptive phenomenological study was carried out. A total of 24 nursing students from a university in the southeast of Spain participated in this study. There were 10 in-depth interviews and two focal groups from January to May 2020. The data analysis was performed using ATLAS.TI software to identify the emergent topics. The COREQ Checklist was used to prepare the manuscript. Three principal topics were identified that illustrated the nursing students’ experiences and perceptions of smartphone use in the clinical setting (1): Using smartphones in the clinical setting as a personal resource, (2) smartphones as a support mechanism for making clinical decisions, (3) impact of smartphones on patient care. The nursing students perceived smartphones as a support mechanism for making clinical decisions and for patient care. Smartphone use during clinical practicums may influence the quality of patient-centred communication and threaten clinical safety. The results of this study provide knowledge on the use of smartphones by nursing students in the clinical setting, which could help to establish measures that guarantee adequate patient care and responsible use of these devices.